“I Did, I Did Taw a Puddy Tat!” Pumas in Urban Ecosystems of Latin America: A Review of the Mediatic Information - Guerisoli, María de las Mercedes; Schiaffini, Mauro Ignacio (Frontiers in Conservation Science, 2022)
The concentration of people living in small areas has increased in the last decades, with more than a half of the world’s population living in cities. This is particularly true for Latin America, a region with no particular high contribution to the world total population, but hosting several large cities. The increase in urbanization causes threats to wildlife, facing discontinues habitat and novel environmental pressures. As the number of wildlife entering cities seems to have increased in the last years, we characterize temporal and geographical events of a widely distributed carnivore, the puma Puma concolor. We performed an exhaustive search for media news regarding sighting, capture and/or kill of pumas within human settlements areas, and tried to relate them with potential explanatory variables. We found a total of 162 events in a period of the last ca. 10 years, particularly concentrated in the year 2020. Most records came from Brazil, Argentina, Mexico and Chile. Of the total, 41% were only sightings, 58% were captures and a minor percentage were considered as mascotism. Almost the same amount of records came from highly populated areas than from low populated areas but with important differences between countries. The countries with more records in urban areas (Brazil and Mexico) showed a larger surface occupied by cities. The countries with most records in rural areas (Argentina and Chile) presents the opposite pattern of occupied surface. This might indicate that different percentages of areas dedicated to cities or urban might explain the differences among countries. The most important variable related to puma events in populated areas was sky brightness, while human density and cattle density explained minor parts. The “anthropause” due to COVID-19 pandemia might explain the larger amount of records from 2020, while the absence of high-quality habitats due to fragmentation and high cattle density, might force the pumas to enter populated areas searching for food. Minor values of night lights could be related to a facilitation of efficiency of foraging behavior. Although some bias might exist in the data, the results should be taken into account as general statements for all analyzed countries.